Perencanaan Optimalisasi Biaya dan Waktu dengan Metode Earned Value pada Proyek Pembangunan Apartemen Embarcadero Bintaro Tanggerang Selatan - Anggreani, Novi; Furuhitho, X; Sulardi, Sulardi; Suparman, Agus; Prakosa, Wahyu (Jurnal Kridatama Sains dan Teknologi, 2024)
Construction projects are closely related to the development of human life needs. To meet this, construction projects must be processed professionally with good management and weight. As one of the functions and processes of activities in project management that greatly affect the final results of the project, planning has an important role in minimizing all irregularities that can occur during the project process. Earned Value is the concept of calculating the amount of costs according to the budget in accordance with the work that has been completed. Cost and time optimization planning is carried out on the Embarcadero Bintaro Apartment Construction Project with the aim of finding out the project performance index, estimated cost and time required, providing alternative solutions to overcome the delays that occur and creating an S curve due to acceleration. The results of the calculation using the Earned Value method show that the project is not running as planned, based on the overall CPI value of > 1. Meanwhile, the SPI value in the 10th week to the 32th week has a value of less than 1, this indicates that the project is experiencing delays. The acceleration carried out to catch up with the delay is to use the crashing method with the most effective acceleration alternative to be applied, namely the addition of 2 hours of overtime to the Column work, by saving the project duration of up to 9 days and an additional cost of Rp. 80.611.591,48 from the normal cost of Rp. 104.928.799.666,42 with a duration after acceleration of 572 days